1984
DOI: 10.1148/radiology.151.1.6701315
|View full text |Cite
|
Sign up to set email alerts
|

Cholescintigraphy in acute cholecystitis: use of intravenous morphine.

Abstract: Conventional cholescintigraphy (60 patients) and a modified protocol (59 patients) were compared in 74 females and 45 males with acute cholecystitis. In the modified protocol, intravenous morphine (0.04 mg/kg) was administered whenever the gallbladder was not seen 40 minutes after injection of Tc-99m-pyridoxylideneglutamate (36/59). Accuracy was 98% with morphine, compared with 88% for the conventional protocol; specificity improved from 83% to 100% with no loss of sensitivity (96% in both groups). Low doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…These risk factors lead to abnormal uptake, excretion of scanning agents, and impaired visualization of the biliary tree, limiting the usefulness of cholescintigraphy in critically ill patients [10,11,27]. Choy et al [12] suggested using morphine to increase common bile duct pressure by contraction of the sphincter of Oddi. This may overcome partial or functional cystic duct obstruction, decreasing the rate of false positives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors lead to abnormal uptake, excretion of scanning agents, and impaired visualization of the biliary tree, limiting the usefulness of cholescintigraphy in critically ill patients [10,11,27]. Choy et al [12] suggested using morphine to increase common bile duct pressure by contraction of the sphincter of Oddi. This may overcome partial or functional cystic duct obstruction, decreasing the rate of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…US is the most accurate noninvasive test for identifying gallbladder disease but is reported to be inconclusive in critically ill patients owing to a high false-negative rate [8,9]. Cholescintigraphy, an alternative diagnostic tool, has a high false-positive rate in critically ill patients [10,11], but when used with morphine sulfate (MC) it has shown improved diagnostic accuracy [12,13]. Numerous retrospective studies have compared US and cholescintigraphy [2,3,9].…”
mentioning
confidence: 99%
“…Many studies have now confirmed the original work of Choy et al [1] and proven that MS-augmented cholescintigraphy is at least as accurate as the delayed imaging method [2][3][4][5]. If the cystic duct is patent, gallbladder filling begins within 5-10 rain of infusing 0.02 mg/kg MS and the entire study can be completed in 60-90 rain, depending on when the drug is infused.…”
Section: Cholescintigraphymentioning
confidence: 90%
“…Morphine has also been used to increase the pressure in the c o m m o n bile duct and thereby increase the likelihood of filling the gallbladder with radiotracer if there is no obstruction in the cystic duct [2].…”
Section: Discussionmentioning
confidence: 99%